2012
DOI: 10.1038/ncomms1835
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally based scaling of leaf venation architecture explains global ecological patterns

Abstract: Leaf size and venation show remarkable diversity across dicotyledons, and are key determinants of plant adaptation in ecosystems past and present. Here we present global scaling relationships of venation traits with leaf size. Across a new database for 485 globally distributed species, larger leaves had major veins of larger diameter, but lower length per leaf area, whereas minor vein traits were independent of leaf size. These scaling relationships allow estimation of intact leaf size from fragments, to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
363
3
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 287 publications
(405 citation statements)
references
References 56 publications
(98 reference statements)
23
363
3
6
Order By: Relevance
“…Briefly, minor veins of fully hydrated leaves were cut under water over a light bench to ensure that no major veins were severed. Cuts were made between about 95% of tertiary veins, yielding 5 to 33 cuts mm 22 depending on sample size (larger leaves have their major veins spaced farther apart, so that fewer but longer cuts were made; Sack et al, 2012;. These cuts were enough for water to move directly out of minor veins and not through outside-xylem pathways (Sack et al, 2004;Nardini et al, 2005).…”
Section: Empirical Measurements Of K Oxmentioning
confidence: 99%
“…Briefly, minor veins of fully hydrated leaves were cut under water over a light bench to ensure that no major veins were severed. Cuts were made between about 95% of tertiary veins, yielding 5 to 33 cuts mm 22 depending on sample size (larger leaves have their major veins spaced farther apart, so that fewer but longer cuts were made; Sack et al, 2012;. These cuts were enough for water to move directly out of minor veins and not through outside-xylem pathways (Sack et al, 2004;Nardini et al, 2005).…”
Section: Empirical Measurements Of K Oxmentioning
confidence: 99%
“…Lobed leaves are generally associated with adaptation to shade [45]; however, in very small leaves lobes are associated with high density of major veins that maintain equable water potential across the leaf under bright conditions [46,47]. Small dissected leaves also enable rapid convective cooling, protecting the leaves from overheating in high light and still air [46,[48][49][50]. Furthermore, the relatively low inferred LMA of Fairlingtonia (electronic supplementary material, S1) is a value typical of herbaceous plants in riparian habitats [34].…”
Section: (B) Ecological Implicationsmentioning
confidence: 99%
“…Previous studies have shown that the pattern of leaf veins and xylem morphology allow a broad range of leaf hydraulic differentiations between species or during development (Sack and Holbrook, 2006;Sack et al, 2012). In addition, living tissues and associated membrane water transport can provide rapid and reversible regulation of leaf water transport capacity (hydraulic conductance) by environmental or physiological cues.…”
Section: Introductionmentioning
confidence: 99%